ANALISIS PENERAPAN AKUNTABILITAS PENGELOLAAN DANA ZAKAT PADA BADAN AMIL ZAKAT DI KOTA MAKASSAR - Mawahib.R, Abul (IDFoS Indonesia, 2024)
The gap between zakat potential and realisation of zakat collection has shown that there are problems in zakat management that need to be addressed. One of them is related to accountability. In relation to zakat institutions, accountability is a form of responsibility for their duties as zakat management. Therefore, as the magnitude of accountability demands, zakat institutions need to improve accountability because it will affect public trust. The focus of this research was on the financial accountability of zakat fund management. The purpose of this research was to determine the application of accountability in the management of zakat funds at BAZNAS Makassar City. This research was a qualitative descriptive research with qualitative methods. Data in the form of primary data and secondary data. Data collection was carried out by observation, interview and documentation. The results showed that the management of zakat carried out by BAZNAS Makassar City in implementing accountability, especially in financial accountability, was quite good but not optimal. This can be seen, first from the supervision system implemented by BAZNAS Makassar City. Supervision is carried out by BAZNAS internal parties and external supervision by the Public Accounting Firm (KAP). The results of this supervision can be seen from the reports that are accounted for to interested parties. Second is the responsibility for BAZNAS's compliance with established rules and laws. The success and responsibility can be seen from the reports that have been audited by the Public Accounting Firm (KAP). Third is the openness of BAZNAS on its information to the public that needs to be maximised. This is due to media management that has not been maximised, the delay of BAZNAS Makassar City in providing information to the public and there is still information that has not been conveyed to the public.